KILKA UWAG O KOLORYSTYCE BAZYLIKI NORBERTANEK W STRZELNIE W XIII-XIV WIEKU - Sulkowska-Tuszyńska, Krystyna (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
The article sums up the reflections on the relics of medieval plaster and layers of paint on the walls, columns and pillars of the Norbertine nuns convent in Strzelno completed around the 2nd-3rd quarter of the 13th century. The relics of the polychromies observed by numerous enthusiasts of the Romanesque Strzelno and discovered during archaeological excavations were topped with the results of conservation-restoration works which uncovered the first figural polychromies in the chancel’s apse. Following verification of the dating of the colours of the church’s interior, an indication was made that in the 13th century, the colour red prevailed; in the 15th-16th centuries, the figural scenes of the apse sported many colours while the remaining part of the sacrum was brightened up with three-colour, geometric patterns. To complete the range of colours, floor tiles were added. Examples have been provided of specialist painting analyses. The entire arrangement has been compared with selected colourful medieval structures. References have been made to the symbolism of the colours used in the Middle Ages and the contemporary, erroneous perception of Romanesque architecture as rustic, devoid of plaster and colours.